Miliary Tuberculosis Presenting With Meningitis in a Patient Treated With Mycophenolate for Lupus Nephritis: Challenges in Diagnosis and Review of the Literature - Precious Macauley MD; Mark Rapp BSc; Sarah Park BSc; Olaoluwatomi Lamikanra MBBS; Pratibha Sharma MBBS; Michael Marcelin MD; Kavita Sharma MBBS (SAGE Publishing, 2018)
Tuberculosis is one of the top 10 causes of death worldwide according to the World Health Organization. Central nervous system involvement is usually the least common presentation of tuberculosis occurring in about 1% of all cases but yet can have very devastating outcomes. Lupus nephritis is one of the most common complications of systemic lupus erythematosus with up to two thirds of patients presenting with some degree of renal dysfunction. The mainstay of treatment is glucocorticoids; however, to sustain remission, steroid sparing agents such as cyclophosphamide, azathioprine and mycophenolate mofetil are used. Such patients, in addition to their baseline dysfunctional immune system, have a heightened risk of infections due to these drugs. In this article, we present a young woman who had recently been started on mycophenolate mofetil for control of class V lupus nephritis who presented with headaches, sinus pressure, and fevers. She had a protracted course of hospitalization as she failed to improve clinically and to respond to conventional therapy for acute bacterial sinusitis and meningitis. She was empirically started on antitubercular therapy 9 days after hospitalization. The diagnosis was not confirmed until day 18, the day results of cerebrospinal fluid acid-fast bacillus culture was reported. This case is reported to highlight the challenges in diagnosing Mycobacterium tuberculosis infection in an immunocompromised state and to demonstrate that its presentation can mimic numerous other conditions. Clinicians must maintain a high index of suspicion of Mycobacterium tuberculosis infection in such patients who present with nonspecific or unexplainable symptoms.